An Eight-year, Single-center Experience on Ultrasound Assisted Thrombolysis with Moderate-dose, Slow-infusion Regimen in Pulmonary Embolism - Kaymaz, Cihangir; Akbal, Ozgur Yasar; Keskin, Berhan; Tokgoz, Hacer Ceren; Hakgor, Aykun; Karagoz, Ali; Konstantinides, Stavros (Bentham Science Publ Ltd, 2022)
Background: There is limited data on moderate-dose with slow-infusion thrombolytic regimen by ultrasound-asssisted-thrombolysis (USAT) in patients with acute pulmonary embolism (PE). Aims: In this study, our eight-year experience on USAT with moderate-dose, slow-infusion tissue-type plasminogen activator (t-PA) regimen in patients with PE at intermediate-high- and high-risk was presented, and short-, and long-term effectiveness and safety outcomes were evaluated. Methods: Our study is based on the retrospective evaluation of 225 patients with PE having multiple comorbidities who underwent USAT. Results: High- and intermediate-high-risk were noted in 14.7% and in 85.3% of patients, respectively. Mean t-PA dosage was 35.4 +/- 13.3 mg, and the infusion duration was 26.6 +/- 7.7 h. Measures of pulmonary artery (PA) obstruction and right ventricle (RV) dysfunction were improved within days (p<0.0001 for all). During the hospital stay, major and minor bleeding and mortality rates were 6.2%, 12.4%, and 6.2%, respectively. Bleeding and unresolved PE accounted for 50% and 42.8% of in-hospital mortality, respectively. Age, rate, and duration of t-PA were not associated with in-hospital major bleeding and mortality. Oxygen saturation exceeded 90% in 91.2% of patients at discharge. During follow-up of median 962 (610-1894) days, high-risk status related to 30-day mortality, whereas age >65 years was associated with long-term mortality. Conclusion: Our real-life experience with USAT with moderate-dose, slow-infusion t-PA regimen in patients with PE at high-and intermediate-high risk demonstrated clinically relevant improvements in PA obstructive burden and RV dysfunction. Age, rate or infusion duration of t-PA was not related to major bleeding or mortality risk, whereas unresolved obstruction remained as a lethal issue.
Keywords: Ultrasound assisted thrombolysis; catheter directed thrombolysis; pulmonary embolism; bleeding; mortality; tissue plasminogen activator